Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Aplikasi Tiktok Dengan Metode Utaut 2 - Sofian Wira Hadi; Ibnu Alfarobi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Humans are social beings who need interaction and communication with others. One of the social media that is often used today is Tiktok. The positive impact on social media includes facilitating user communication throughout the world who use communication tools in social media. Several previous studies examining the factors that drive the use of a system show that the UTAUT model is proven to be able to explain the acceptance of a technology. From the results of Habbit research, Performance Expetancy, and Social Influence have a positive effect on BI or interest in using the tiktok application and affect the use of the tiktok application. These three variables have significant values ​​that are different from Performance Expetancy and Habit which have a fairly high significant value for interest in using the tiktok application.